Possibility of Bypassing Three Fractured Rotary NiTi Files and Its Correlation with the Degree of Root Canal Curvature and Location of the Fractured File: An In Vitro Study - Arshadifar , Esmaeil; Shahabinejad, Hasan; Fereidooni , Rahim; Shahravan, Arash; Kamyabi , Homa (Iranian Endodontic Journal, 2022)
Introduction: This study aimed to evaluate the success rate of bypassing three NiTi rotary files (RaCe®, Hero 642®, and K3®), fractured in various root canal locations of extracted mandibular molars with two different canal curvatures. Materials and Methods: Ninety freshly extracted human first or second mandibular molars were selected. Three millimeters of the file tip (RaCe®, Hero 642®, and K3®), was fractured intentionally in the mesiobuccal root canal of each tooth by weakening the file in the last 3 mm of files #30 with 4% taper and preparing the root canals with two different degrees of curvature (n=30). Then, bypass possibility of the fractured files was evaluated using #8, #10, and #15 K-files and compared in different groups. In addition, the rate of accidental procedural errors was compared between these groups. Data were analyzed with univariate analysis and logistic regression models at a significance level of 0.05. Results: The overall success rate of bypassing was 61.1%. RaCe® files had the highest and the K3® files had the lowest bypass possibility rates (P=0.01); the greater the degree of canal curvature, the less successful the bypass procedure (P=0.01). The fracture of the files used to bypass was the most prevalent error. Conclusion: Based on this in vitro study the type of fractured file and the amount of canal curvature affected the success rate of the bypassing technique. In RaCe® files and the mild curvature group, the success rate was the highest.